Adoption of Digital Breast Tomosynthesis in Clinical Practice - Richman, Ilana B. (JAMA Intern Med, 2019)
This study uses administrative claims from an insurance database to examine adoption of digital breast tomosynthesis for cancer screening and describe regional patterns and sociodemographic characteristics associated with its use.